THE DEEP BREATHING EXERCISE MORE EFFECTIVE THAN DIAPHRAGMATIC BREATHING EXERCISE TO INCREASE LUNG VITAL CAPACITY ONELDERLY PEOPLE IN BANJAR KEDATON, TONJA VILLAGE, DENPASAR TIMUR DISTRICT - Putri, I Dewa Ayu Juniastari; Wibawa, Ari; Primayanti, I Dewa Ayu Inten Dwi; Wiryanthini, Ida Ayu Dewi (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Problems that will appear from the reduction in lung vital capacity is the decrease the amount of oxygen that can be consumed by the elderly that would affect his health. This study design was Randomized Pre Test and Post Test Control Group Design involving 24 people were then divided into two groups. The test results show paired samples t-test p=0.000 in group I ( deep breathing exercise ) and group II ( diaphragmatic breathing exercise ). The test results show independent t-test p=0.000 the difference of vital lung capacity, conclusionis deep breathing exercise effective in improving lung vital capacity than diaphragmatic breathing exercise in the elderly. Keywords: lung vital capacity, deep breathing exercises, diaphragmatic breathing exercise, the elderly.